Dinamika Tim Audit Dan Kualitas Audit - Yefta Andi Kus Nugroho; Dyah Ekasari Sekar Jatiningsih (Universitas Airlangga, 2013)
Audit quality is an important outcome of the work performed by audit team. Works of audit firm generally performed by team and teamwork performance will lead to a good audit quality. Good audit quality, in turn, will result in good audit report. Related to the interaction among audit team members, some factors that need to be highlighted is the structure or composition of the team, communication among team members, and effective use of time. This research intend to explore audit team dynamics in constructing audit quality. The test of audit team dynamics effect on audit quality is performed through a survey research toward auditors who work in audit firms. Result shows that significant aspect of audit team dynamics which affect audit quality are communication and effectiveness of audit time.